Periodontal Disease Associated with Higher Risk of Dementia: Population‐Based Cohort Study in Taiwan. Issue 9 (9th June 2017) - Lee, Ya‐Ling; Hu, Hsiao‐Yun; Huang, Li‐Ying; Chou, Pesus; Chu, Dachen
Abstract : Objectives: To determine the magnitude and temporal aspect of the effect of poor dental health and periodontal disease (PD) on dementia. Design: Retrospective cohort study Setting: Taiwan National Health Insurance Research Database. Participants: Individuals with newly diagnosed PD (N = 182, 747) Measurements: Participants were followed from January 1, 2000, to December 31, 2010. Participants were assigned to dental prophylaxis, intensive periodontal treatment, tooth extraction, or no treatment, according to International Classification of Diseases codes and PD treatment codes. The incidence rate of dementia of the groups was compared. The association between PD and dementia was analyzed using Cox regression, with adjustments for age, sex, monthly income, residential urbanicity, and comorbidities. Results: The incidence of dementia was significantly higher in the group with PD that did not receive treatment (0.76% per year) and in the group that had teeth extracted (0.57% per year) than in the group that underwent intensive PD treatment (0.35% per year) and the group that received dental prophylaxis (0.39% per year) ( P < .001). After adjusting for confounders, the Cox proportional hazards model revealed a higher risk of dementia in the group with PD who did not undergo treatment (hazard ratio (HR) = 1.14, 95% confidence interval (CI) = 1.04–1.24) and the group that had teeth extracted (HR = 1.10, 95% CI = 1.04–1.16) than in the group that received dental prophylaxis. Conclusion: Subjects who had more severe PD or did not receive periodontal treatment were at greater risk of developing dementia.